Southpaw : a sideshow of boxing's big show - Baker, Richard E. ([publishers not identified], 2017)
"Richard Baker believes truth should not be boring. The life of heavyweight boxer Chauncy Welliver is anything but boring. In this liberally enhanced account Baker has elevated the story to the art of historical fiction much like Truman Capote did with his non-fiction novel "In Cold Blood". Welliver, a better fighter than most people realized appeared to fight constantly and everywhere. He represents the thousands of working professional boxers around the world who step into the ring and risk physical and mental damage in an attempt to earn a living. Welliver has lived through the highs and lows of boxing, the crooked deals, the occasional decent money, the ridiculous pay-days, the lies and cheating, the under-table deals, the cheers and boos of crowds, all for the satisfaction of experiencing a vivid and rich life filled with both joy and heartbreak."-- back cover